A Crescent Biface from Southeastern Utah. (2nd April 2020) - Tune, Jesse W.; Fox, Jon M.
ABSTRACT: Crescent bifaces are one of the most enigmatic stone tool types in North America. While these artifacts are poorly understood, they are widely known from sites throughout a core area consisting of the Great Basin and California. Here, we report on one of the eastern-most crescents from southeastern Utah, which is also the only crescent currently documented from the northern Colorado Plateau.